Pemberdayaan Masyarakat di Desa Lakekun Melalui Pelatihan Kewirausahaan Berbasis Pangan Lokal di Desa Lakekun Kecamatan Kobalima Kabupaten Malaka Propinsi Nusa Tenggara Timur (Studi Kasus Kios Kue K2) - Ermalinda Taek Naimnule; Maria Yunita A Bano; Veronika Y Luruk; Sirilus Lake; Mardit N.Nalle (Jurnal Nusantara Berbakti, 2023)
Kada Cake Kiosk is one of the Micro, Small and Medium Enterprises that has seized the opportunity to develop Banana Chips as processed food in Kobalima District. Even though Kobalima District has made a small contribution in developing Micro, Small and Medium Enterprises in Malacca Regency, this potential can become a business opportunity for K2 Cake Kiosk owners in developing these processed foods. The idea of developing a banana chip business began in 1993 when Ms. Sipriana Hoar wanted to develop a banana chip business with minimal capital but had the potential to increase business income. This is done by moving from developing chips and other processed food businesses to processing products that have the potential to increase product-added value. This business analysis originates from existing recipes from their parents in micro businesses as snacks or snacks. This opportunity, where the bananas cultivated by farmers sometimes have a low selling value, was utilized by Ms. Sipriana to increase her business in banana chips and other processed foods. The method of carrying out the Professional Work Practice activities of the Agribusiness Study Program, Faculty of Agriculture, University of Timor, provides solutions to the problems identified in Lakekun Village, especially at the K2 Cake Kiosk. The method of carrying out the intended activity is purposive, namely the intentional determination of the K2 Cake Kiosk as the main indicator that is used as a respondent in carrying out the intended activity. The approach taken in answering problems such as: 1. Location surveys, namely looking at existing potentials and constraints such as Community Problems in the Benpasi Village.2. Identification of each Community that can be used as an example of the intended entrepreneurship training. 3. Training for each farmer group in the Benpasi Village to answer these problems to increase agricultural production in the Benpasi Village. 4. Counseling and training on maintenance and care management for plants so that they can be used for further processing 5. Monitoring and evaluation of the activities in question in an effort to increase the intended community service activities. From the Training Activities for Making Banana Chips at the K2 Cake Kiosk in Lakekun Village,Kobalima District, Malaka Regency, East Nusa Tenggara Province based on Professional Work Practices in the Agribusiness Study Program, Faculty of Agriculture, University of Timor, it can be concluded that students can see business potential and are able to analyze the advantages possessed in micro-businesses in Lakekun Village. In addition, they get a lot of benefits from the training by providing recipes that are obtained by business owners so that in the future they can be practiced as business opportunities.